Flores-ser na profissão: a construção da profissionalidade docente de professoras aposentadas - Ariadne Cristiane Fantoni Silva (2021)
Of a qualitative nature, the research recognizes the teacher as a protagonist, holder and builder of knowledge and its professionalism. The objective is to discuss the construction of the professionalism of retired teachers from the initial grades of elementary school, who joined the Municipal Education Network of Belo Horizonte (RME/BH) in the 1980s, based on their narratives. In this study, it is understood that retired teachers, when narrating their professional trajectories, point out elements of the ways of being, being and know-how in the teaching profession, which imply in the construction of their professionalities. These professional stories were collected through narrative interviews (SCHÜTZE, 2014) recorded during individual meetings with five retired teachers. The narrative interviews were analyzed using the "comprehensive-interpretative analysis" procedure (SOUZA, 2014). This research is situated in the theoretical-methodological field of narrative research that recognizes the potential of narratives as a method and source of knowledge. It is based on the theoretical reference of Bruner (1991) and Benjamin (1994); for questions related to professionalism we selected Sacristán (1995) and Roldão (2005,2007); on the teaching work we found Tardif and Lessard (2007) and for the teaching knowledge we used Nóvoa (1995), Tardif (2002) and Gauthier (2013). The narratives highlighted the teachers' perceptions of the continuous learning process of the teacher, revealing in their memories the personal, affective and formative references they had in life: the family, the school as a student, the "model" teachers; initial and continuing formation, interactions with students, exchanges with co-workers and in the various professional experiences. These dimensions, linked, make up the knowledge-teaching, the know-how, the knowledge-being and the know-how in the profession and which constitute a true collective history of the teaching profession. The research proposes as a final product a digital record through the e-book that makes it possible to share aspects related to the knowledge about how retired teachers understand the events of their professional trajectories, relating them to the process of building professionalism.